(3aVGFd cJGH GdLGeY ddJQePjs - (3eMeO Hf YjSi Hf ShQI Hf ehSi GdSdej GdHhZj GdJQePj, CHh YjSi ,J (B279 (3g` s
(3ChdgG (B:s
(3hHYO aEf Yde GdGKQ GTQa GdYdhe ai GdeYGO hGQLCgG YfO QH GdYHGO hdg CFeI hLgG HPI hfbGO YOdhG QLGdg hLQMhG hTQMhG CdaGXg s
(3BNQgG (B:s
(3haVd GdYde jXgQ MjHf jfCi Yf GdGQhGM eCdha GdLShe hUd eOG GdReGf Ydi QShd jahM dPcQg CQL GdfSjf BNQ GdLRA HaVGFd LGeY GdJQePi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydjg SeGYGJ YOjOIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs